Economic and Health Dimension of Female Labor Force Participation in Indonesia - Kurniasari, Wulan; Budiarty, Ida; Murwiati, Asih (Jurnal Ekonomi Pembangunan, 2025)
Women and employment are a problem faced by both developed and developing countries. The view that women should work in the domestic sphere places women as weak and disadvantaged in society. This study aims to analyze and determine the role of the dimensions of economic and health in the female labor force participation during the 2017-2021 period in 34 provinces in Indonesia. Economic indicators are seen from female wages and female education. Meanwhile, health indicators are seen in female-headed households, fertility, and young women’s marriage. This study uses panel data analysis with the Fixed Effect Model (FEM). The study results show that the indicators in the economic dimension that have a significant relationship to the female labor force participation are female wages and female education. Then, an indicator in health that has a significant relationship is early-age marriage. Education emerges as a key finding in this study, thereby positioning the expansion of women's access to education as a central focus in efforts to enhance female labor force participation (FLFP).